2017
DOI: 10.1172/jci.insight.89798
|View full text |Cite|
|
Sign up to set email alerts
|

An early-biomarker algorithm predicts lethal graft-versus-host disease and survival

Abstract: No laboratory test can predict the risk of nonrelapse mortality (NRM) or severe graft-versus-host disease (GVHD) after hematopoietic cellular transplantation (HCT) prior to the onset of GVHD symptoms. Patient blood samples on day 7 after HCT were obtained from a multicenter set of 1,287 patients, and 620 samples were assigned to a training set. We measured the concentrations of 4 GVHD biomarkers (ST2, REG3α, TNFR1, and IL-2Rα) and used them to model 6-month NRM using rigorous cross-validation strategies to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(97 citation statements)
references
References 36 publications
4
93
0
Order By: Relevance
“…The serum level of the soluble form of ST2 was reported to be an important biomarker for therapy-resistance in patients developing acute GVHD 71 . Based on this observation an early-biomarker algorithm was studied for its predictive value for lethal acute GVHD 72 . A 4-biomarker panel [ST2, TNFR1, IL-2Rα chain(CD25), regenerating islet-derived protein-3 alpha(REG3α)], released from injured tissue or activated T effs , was used to predict increased acute GVHD-related death.…”
Section: Biomarkers For Agvhd Severity - Studies In Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum level of the soluble form of ST2 was reported to be an important biomarker for therapy-resistance in patients developing acute GVHD 71 . Based on this observation an early-biomarker algorithm was studied for its predictive value for lethal acute GVHD 72 . A 4-biomarker panel [ST2, TNFR1, IL-2Rα chain(CD25), regenerating islet-derived protein-3 alpha(REG3α)], released from injured tissue or activated T effs , was used to predict increased acute GVHD-related death.…”
Section: Biomarkers For Agvhd Severity - Studies In Patientsmentioning
confidence: 99%
“…A 4-biomarker panel [ST2, TNFR1, IL-2Rα chain(CD25), regenerating islet-derived protein-3 alpha(REG3α)], released from injured tissue or activated T effs , was used to predict increased acute GVHD-related death. By modeling 6-month non-relapse mortality in an independent test set and validation set, a 2-biomarker model using ST2 and REG3α concentrations identified patients with a cumulative incidence of 6-month nonrelapse mortality of 28% in the high-risk and 7% in the low-risk group 72 .…”
Section: Biomarkers For Agvhd Severity - Studies In Patientsmentioning
confidence: 99%
“…The efficacy analysis population was composed largely of adults with grades 3–4 (73%) GVHD; most had undergone transplantation using peripheral blood stem cells (80%) from a matched related or unrelated donor (76%). The cohort had a median MAGIC biomarker score of 0.47, and 83% were in the MAGIC biomarker high‐risk group . The median duration of prior corticosteroid exposure at baseline was 15 days (range: 3–106 days).…”
Section: Efficacymentioning
confidence: 99%
“…REG3α is secreted primarily by Paneth cells and functions as an antimicrobial peptide and regulator of Gram-positive bacteria in the gut 47 . A large study ( n = 1,287) that utilized a two-biomarker signature measuring ST2 and REG3α concentrations in the blood 1 week after HSCT identified patients who were at high risk of developing lethal GVHD (~20%) and reported a cumulative incidence of 6-month non-relapse mortality (NRM) of 28% in the high-risk group compared with 7% in the low-risk group ( P < 0.001) 48 . Compared with the low-risk group, high-risk patients had a significantly greater GVHD-related mortality (4% versus 18%, P <0.001) and risk of severe gastrointestinal acute GVHD (8% versus 17%, P <0.001).…”
Section: Diagnosismentioning
confidence: 99%
“…Patients who present with only skin involvement at the time of diagnosis are classified as AA3 (high risk) by their bio-marker profiles and are twice as likely to develop gastrointestinal acute GVHD compared with patients who are classified as AA1 (low risk) 49 . The two-biomarker AA algorithm is superior to the three-biomarker algorithm, as it can accurately identify more patients who are at low risk, which is perhaps a result of the adoption of a commercial enzyme-linked immunosorbent assay (ELISA) that has increased sensitivity for detection of ST2, the best single biomarker, compared with that used when the initial three-biomarker AA algorithm was developed 48 . Although promising, this algorithm is currently best used in the context of a clinical trial, as it has not yet been demonstrated that a therapeutic intervention based on the biomarker risk can change long-term outcomes.…”
Section: Diagnosismentioning
confidence: 99%